The Effect Of Emotional Intelligence and Learning Motivation on Students' Learning Outcomes In Social Studies - Marwansyah, Marwansyah; Syahrin, Alfi; Muharramsyah, Rambang (Journal Prakarsa Paedagogia, 2024)
The purpose of this study is to describe the influence of emotional intelligence and learning motivation on student learning outcomes in social studies. The research method used is quantitative research. The design in this study is correlation research, by looking at the existing variables, namely the correlation of two independent variables, namely emotional intelligence and student learning motivation and one dependent variable, namely student learning outcomes. Furthermore, the description as an illustration of the research design is to find out the perspective or a frame of reference and view a theory proposed in the research of hypothesis testing and to find out whether or not there is an influence between variables. The data collection technique used in this study was a planned interview with student respondents in the research area. While data that cannot be collected by interview, this study also uses observation techniques. The results of the study showed that the magnitude of the influence of emotional intelligence and learning motivation simultaneously (at the same time) on social studies learning outcomes can be seen from the results of the determination coefficient, which is 0.726. Thus, the magnitude of emotional intelligence and learning motivation simultaneously on social studies learning outcomes in elementary schools in Cluster 2, Pegasing District is 72.6%. However, for further research, it is recommended to expand the research object.